Comparison of Radiofrequency Ablation and Steroid Injection in the Treatment of Plantar Fasciitis; Short and Medium Term Results - Mahmut Sert; Ahmet Yurteri (Genel Tıp Dergisi)
Objective: Plantar fasciitis, commonly found in orthopaedic practice, may restrict daily life activities and lead to loss of workforce. We aimed to evaluate the short- and medium-term outcomes of radiofrequency ablation (RFA) and steroid injection treatments in patients with plantar fasciitis who did not benefit from conservative therapies through pain and function scores. Material and Method: Patients studied at the Hakkari State Hospital for at least six months of conservative treatment due to plantar fasciitis between 01.07.2021-01.01.2023. The patients were divided into two groups: those who received RFA and those who were given steroid injections. Demographic information of the patients, the Visual Analog Scale (VAS) and the American Orthopedic Foot Ankle Society (AOFAS) score were studied, and both gups were compared. Results: No significant difference was observed when comparing preop VAS and AOFAS values for both groups (p=0.469 p=0.244). No significant difference was observed when comparing the VAS and AOFAS values of the two groups for the first month (p=0.764 p=0.466 respectively). A significant difference was observed when comparing the VAS and AOFAS values in the post-6 month (p=0,001 p=0.001). Significant differences were observed between VAS and AOFAS values in patients receiving RFA in preop and 6 months (p=0.001 p=0.001). No significant difference was observed in preop and 6 month VAS and AOFAS values in steroid injections (p=0.512 p=0.844 respectively).No complications were observed in both groups during the follow-up period. Conclusion: In patients who have received conservative treatment but have not benefited, radiofrequency ablation has been found to be an effective, safe and minimally invasive method of reducing the severity of pain in the short to medium term and improving daily activities.